Inflammatory focal bone destruction in femoral heads with end‐stage haemophilic arthropathy: a study on clinic samples with micro‐CT and histological analyses. (20th September 2015) - Zhang, S.; Lu, C.; Ying, J.; Wang, P.; Xu, T.; Chen, D.; Jin, H.; Tong, P.
<x xml:space="preserve">Abstract</x> Introduction Focal bone destruction has a high prevalence in haemophilic arthropathy (HA) affected joints, but the mechanism remains unclear. Aim We undertook this study on clinic samples to explore the focal bone destruction in femoral heads suffered with end‐stage HA. Methods Twenty‐one femoral heads from HA patients and 19 femoral heads from rheumatoid arthritis (RA) patients were scanned by micro‐CT. Histological analysis, including TRAP staining of subchondral bone were performed to evaluate the bone destruction and osteoclasts activity. RANKL, OPG as well as pro‐inflammatory cytokines, such as TNF‐α and IL‐1β in subchondral bone were detected by immunohistochemistry (IHC) method. Results Severe focal lesion was observed in all the HA and RA femoral heads by micro‐CT imaging and histological analysis. The mean percentage of lesion volume to total volume of the femoral heads from HA patients was significantly higher than those from RA patients. There was no significant difference in osteoclasts numbers in subchondral bone between HA and RA groups. By IHC analysis, high expression of RANKL, TNF‐α, IL‐1β and low expression of OPG and RANK were observed in subchondral bone, and there were no significant differences in the expression of RANKL, OPG, RANK, TNF‐α and IL‐1β in femoral heads derived from HA and RA patients. Conclusion Our findings demonstrated the focal bone destruction coupled with inflammatory osteoclastogenesis at subchondral bone in femoral heads from patients with end‐stage HA, and that was similar to the changes in the femoral heads of RA patients.